PARAPHILIA AND MAJOR DEPRESSIVE DISORDERS: PREVALENCE AND PATHOGENESIS - Rahman, Pramudyo Aula (Journal of Psychiatry Psychology and Behavioral Research, 2024)
Introduction - Paraphilia disorders are defined as an abnormal intense sexual deviant followed by behaviors to fulfill fierce sexual erotic activities. Major depressive disorder (MDD) is a mood disorder marked by the appearance of a depressed mood, decreased interest, poor cognitive function, and vegetative symptoms including sleep or eating disorders. There is a study about the prevalence of paraphilia in the US, 15,9%. Meanwhile, there is about 6,1% of the prevalence of depressive disorders in Indonesia. According to DSM-5, Paraphilias, and paraphilia-related disorders, depressive disorders are the most frequent comorbid axis I diagnoses with a lifetime prevalence of life by 56%. Based on these case numbers, this study aims to discuss the correlation between these two events. Methods - Researchers used several journals and textbooks discussing the prevalence and pathogenesis of paraphilia and major depressive disorders; and the correlation between these two disorders. Results - Paraphilias are rarely diagnosed in clinical settings because many cases of paraphilia are related to illegal and criminal acts (such as sexual harassment), and reporting methods are unreliable, meanwhile depression is ubiquitous in both high and low-income countries. This shows that any government needs to be aware of the effects of depressive disorders. Those who have not sought treatment are still high, amounting to 87 to 91% of depressive disorders that have not sought treatment. Discuss - There is a significant correlation between paraphilia and major depressive disorder, MDD is one of the paraphilia-related disorders comorbid axis I diagnosis with a lifespan prevalence of 56%. From the pathogenesis, monoamine neurotransmitters dopamine, norepinephrine, and serotonin serve a modulatory role in human sexual motivation, appetitive, and consummatory behavior. Conclusion - In pathogenesis, there's a degradation in function, amount, and production of neurotransmitter monoamine, dopamine, norepinephrine, and serotonin that cause the person with paraphilia usually show symptoms such as mood changes, decreased interest, depression, decreased cognitive function, and the appearance of vegetative-related symptoms such as impaired appetite or sleep activity. Keywords: paraphilias, depression, pathogenesis.